Reforming the Labour Market in Spain - Wölfl, Anita (OECD Economics Department Working Papers, 2011)
After steady employment growth since the 1990s, Spain has experienced the sharpest increase in unemployment among OECD countries during the crisis, amplified by structural problems of the labour market. Very high de facto severance payment of permanent contracts has resulted in a rigid dual market with adverse effects on unemployment and productivity. The collective wage bargaining system has hindered firms from adapting to macroeconomic shocks exacerbating their negative effects on the labour market. The recent labour market reform legislation is a positive step to reduce excessive protection of workers in permanent contracts, although some uncertainty remains on how courts will interpret it. It also makes it easier for firms to opt out from higher level collective agreements. The large drop-out rate from lower secondary education is an important factor explaining very high unemployment among young workers. Better access of young people to training is an effective tool to keep them out of a depressed labour market. Finally, the matching of people to jobs, notably through the public employment services, needs to be made more efficient, all the more so under currently tight fiscal constraints. Although the recent reform allows private for-profit firms to provide placement services, more needs to be done. Performance of regional public employment services should be benchmarked and incentives of unemployment benefit recipients to search for a job increased